Faktor-Faktor Yang Mempengaruhi Tingkat Kepuasan Hunian Perumahan Bersubsidi Di Kota Malang - Agus Inter Arma Caritas; Wisnumurti Wisnumurti; Agus Suharyanto (Rekayasa Sipil, 2017)
The city of Malang is one of the largest cities in East Java will not be separated from the problem of housing needs. However, there are still many people who do not have homes, especially for low-income people. In meeting the needs of homes, low-income residents find it difficult to have cash in house and limited costs. Therefore, the government provides a program to facilitate the residents in meeting the needs of the house that is with the program Housing Financing Liquidity Facility (FLPP). This study aims to increase the role of stakeholders in building subsidized housing as measured by the level of satisfaction of residents in subsidized housing in Malang. Analyzes for the support used include descriptive analysis to explain the occupants' satisfaction for each housing sample. And the method used is the importance-performance analysis (IPA), Customer Satisfaction Index (CSI) and Regression. After the results of data processing, obtained the results of the level of customer satisfaction assessing the performance of subsidized housing developers in Malang included into the category either, Index Performance) totaling 67.02%. And where variable of location factor, building quality factor, and completeness factor of facility and infrastructure have positive influence to satisfaction of subsidized housing resident in Malang City.